Two and three point one-step block methods for solving delay differential Eequations (Kaedah blok satu langkah dua dan tiga titik bagi penyelesaian persamaan pembezaan Lengah) - Hazwani Mohd Radzi,; Zanariah Abdul Majid,; Fudziah Ismail,; Mohamed Suleiman, (Penerbit Universiti Kebangsaan Malaysia, 2012)

(untitled)
In this paper, initial value problems of first order delay differential equations (DDEs) are solved using two and three point one step block method. Neville’s interpolation will be implemented for the solutions of the delay argument. The general formulation of one-step block method for solving ordinary differential equations is adapted to solve DDEs. The P- and Q-stability are also discussed. Numerical results are given to illustrate the performance of those block methods for solving delay differential equations.